How should evaluation be? Is a good evaluation of research also just? Towards the implementation of good evaluation - Cinzia Daraio; Alessio Vaccari (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2021)
In this paper we answer the question of how evaluation should be by proposing a good evaluation of research practices. A good evaluation of research practices, intended as social practices à la MacIntyre, should take into account the stable motivations and the traits of the characters (i.e. the virtues) of researchers. We also show that a good evaluation is also just, beyond the sense of fairness, as working on good research practices implies keep into account a broader sense of justice. After that, we propose the development of a knowledge base for the assessment of "good" evaluations of research practices to implement a questionnaire for the assessment of researchers' virtues. Although the latter is a challenging task, the use of ontologies and taxonomic knowledge, and the reasoning algorithms that can make inferences on the basis of such knowledge represents a way for testing the consistency of the information reported in the questionnaire and to analyze in a correct and coherent way the data gathered through it.
Keywords: I2; I23; 330; research evaluation; research practices; virtue ethics; good evaluation; fair evaluation; just evaluation; ontology-based modelling; questionnaire